Band-shaped handle part of drinking bottle - MAGATA SHINICHIRO (2011)
A drinking water bottle for a beverage server has a capacity as large as 5 to 20 liters so that it needs a handle for its handling. The handle has been attached by molding it separately at the blow-molding time of the beverage bottle, so that it has a high percent defective at the molding time and a low strength. In order to solve this problem, there is molded a band-shaped handle part having handles separated at the two ends of a band. This handle part is fixed by winding it on the beverage bottle, and the handle is mounted to make it possible to reduce the percent defective at the beverage bottle molding time and to elongate the time period for the repeated use of the handled beverage bottle. It is also possible to facilitate the selecting work at the time of disposing the handled beverage bottle and to recycle the material. By mounting a cushion member acting as a slip stopper on such a face of the band-shaped handle part as contacts the beverage bottle, moreover, the mounted handle can prevent a play and